Student´s perspective of the study plan of the Sociology career of the Universidad Nacional of Costa Rica - Chaverri Chaves, Diego (2022)
This article shows quantitative research about the study plan of the school of Sociology of the Universidad Nacional, which undertook the updating of its study plan; for this purpose, opinions were taken from the student community that went from the third to the sixth year of the degree; for a total of 137 students. This quantitative research, consisted of an instrument that addresses the five areas of the study plan, namely: 1) Social Reality, 2) Sociological Theory, 3) Epistemology and Methodology, 4) Technical and Instrumental and 5) Optional; measured through a Likert scale and an open question to capture other related aspects. The main findings highlight that the performance of the study plan is not homogeneous for its students, some areas have high marks, others do not, in addition, it is observed that students of the last levels are less pleased with their study plan, compared to students of previous levels. Finally, in the open question, the student population tends more to offer suggestions for improvement than disagreements, highlighting the importance of attending the quality of teaching and the pedagogical and andragogical processes. Based on the results obtained, difficulties are identified in separating the study plan appreciation from the assessment of the teaching staff, it is also recommended to restructure and delimit with greater clarity the areas of the study plan, stimulate and accompany the didactic training of the teaching staff in the implementation of the career, and integrate more constantly the theoretical and practical aspects in the educational training.